20 Minute Manager - Harvard Business Review (Boston HBR, 2014)
You?ll get up to speed fast on the most essential business skills with this set of concise, practical primers. Finance Basics explains the fundamentals of corporate finance—and its jargon; Running Meetings gives you the tools and checklists you need to keep your meetings effective and efficient; Presentations helps you create and deliver a persuasive performance, fast; Managing Projects shows you how to set up and execute on a project plan; Managing Time helps you to figure out where all the minutes of your day are going—and how to get them under control; Getting Work Done helps you to use each of those minutes more productively; Creating Business Plans shows you how to present the risks and rewards of your idea; Managing Up helps you to build your relationship with your boss; Delegating Work shows you how to hand work off right; and Giving Effective Feedback teaches you how to make potentially difficult confrontations and turn them into productive conversations. This 10-volume, specially priced boxed set makes a perfect gift for aspiring leaders who are short on time but need advice fast.
Includes Index
Keywords: Presentations